2017
DOI: 10.1016/j.foodres.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Novel bioactive peptides from enzymatic hydrolysate of Sardinelle ( Sardinella aurita ) muscle proteins hydrolysed by Bacillus subtilis A26 proteases

Abstract: Sardinelle protein hydrolysate (SPH), prepared by treatment with Bacillus subtilis A26 proteases, was found to exhibit antibacterial, antioxidant and ACE-inhibitory activities. SPH, with a degree of hydrolysis of 4%, was fractionated by size exclusion chromatography on a Sephadex G-25 into five major fractions (F1-F5). F2, which exhibited the highest antibacterial and ACE-inhibitory activities, and F4, which exhibited the highest antibacterial and antioxidant activities, were further fractionated by reverse ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…Useful antioxidant peptides have also been obtained through fermentation (He et al, ) or by chemical synthesis based on the sequences of peptides identified from food proteins (Gallego et al, ; Jin, Liu, Zheng, Wang, & He, ). In a couple of recent reports, microbial enzyme preparations were employed for the liberation of antioxidative cryptides (specific amino acid sequences encrypted within the primary structure of various food proteins) from their parent vegetable (Babini, Tagliazucchi, Martini, Dei Più, & Gianotti, ) and fish muscle (Jemil et al, ) proteins.…”
Section: Production Of Antioxidant Enzymatic Protein Hydrolyzatesmentioning
confidence: 99%
“…Useful antioxidant peptides have also been obtained through fermentation (He et al, ) or by chemical synthesis based on the sequences of peptides identified from food proteins (Gallego et al, ; Jin, Liu, Zheng, Wang, & He, ). In a couple of recent reports, microbial enzyme preparations were employed for the liberation of antioxidative cryptides (specific amino acid sequences encrypted within the primary structure of various food proteins) from their parent vegetable (Babini, Tagliazucchi, Martini, Dei Più, & Gianotti, ) and fish muscle (Jemil et al, ) proteins.…”
Section: Production Of Antioxidant Enzymatic Protein Hydrolyzatesmentioning
confidence: 99%
“…Therefore, suitable separation and purification methods are needed to enrich peptide fragments with high antioxidant activity. At present, the commonly used purification strategies for PAs mainly include membrane and chromatographic separation technology based on the changes of Mw, charge and polarity/hydrophobicity [ 153 , 154 ]. The membrane separation technology, containing microfiltration, UF and nanofiltration, is cheap and easy to operate, often applied for the initial purification [ 155 ].…”
Section: Purification and Identification Of Pasmentioning
confidence: 99%
“…Hydrolysed collagens or gelatin hydrolysates from fish origins have attracted an increasing interest for consumers as potential ingredients for various health-promoting benefits. Bioactive peptides from marine sources with antioxidant properties have gained attention as pharmaceuticals and functional ingredients (Jemil et al, 2017;Neves et al, 2017). Hydrolysed collagens from fish skins have been reported to contain biologically active peptides with several bioactivities (Sae-leaw et al, 2016a;Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%